2015
DOI: 10.1088/1468-6996/16/4/043502
|View full text |Cite
|
Sign up to set email alerts
|

Growth and applications of GeSn-related group-IV semiconductor materials

Abstract: We review the technology of Ge1−xSnx-related group-IV semiconductor materials for developing Si-based nanoelectronics. Ge1−xSnx-related materials provide novel engineering of the crystal growth, strain structure, and energy band alignment for realising various applications not only in electronics, but also in optoelectronics. We introduce our recent achievements in the crystal growth of Ge1−xSnx-related material thin films and the studies of the electronic properties of thin films, metals/Ge1−xSnx, and insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 153 publications
(178 reference statements)
1
110
0
3
Order By: Relevance
“…Intrinsic bulk Ge is an indirect band-gap material, but it can be converted to a quasi-direct band gap material due to the small separation between the  and L valley (136 meV) [1]. It was shown that the direct band gap of Ge can be realized by tensile strain engineering, alloying with Sn or ultra-high n-type doping [2][3][4][5]. By using only one of these methods it is extremely difficult to achieve a direct band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic bulk Ge is an indirect band-gap material, but it can be converted to a quasi-direct band gap material due to the small separation between the  and L valley (136 meV) [1]. It was shown that the direct band gap of Ge can be realized by tensile strain engineering, alloying with Sn or ultra-high n-type doping [2][3][4][5]. By using only one of these methods it is extremely difficult to achieve a direct band gap.…”
Section: Introductionmentioning
confidence: 99%
“…GeSn alloy grown by CVD usually shows better uniformity and crystalline quality than that by MBE. 15 Almost all GeSn samples that are capable of obtaining light emission are grown by CVD, including the first photoluminescence (PL) results, 16 the first GeSn laser, 12 etc. On the other hand, for the GeSn alloys with ultra-high Sn contents are grown by MBE.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are also some reports on the synthesis of GeSn [21][22][23] and SiGe [20,24,25]. However, there is no experimental report on the synthesis of SnC.…”
Section: Introductionmentioning
confidence: 99%